Gliosarcomas: A Rare Case Report at Viet Duc University Hospital and Review of the Literature - Thi Quynh, Nguyen; Duc Hoan, Nguyen; Thi Luan, Dao; Tung Ngoc, Nguyen; Sy Lanh, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 2, 2021)
Gliosarcoma is a rare biphasic subtype of glioblastoma with the poor prognosis, principally affects adults; males are more frequently affected, with a male-to-female ratio of 1.8/1. Gliosarcomas are usually located in the cerebral hemispheres, involving the temporal, frontal, parietal, and occipital lobes in decreasing order of frequency. Rarely, gliosarcomas occur in the posterior fossa, lateral ventricles, or spinal cord. A case study: A 32-year-old woman presented with persistent nausea and headache. The preoperative diagnosis was Ependymoma in the right lateral ventricle of the brain. The patient underwent surgical resection of the tumor followed by external radiotherapy, and chemotherapy treatment. Histologic description: The tumor was made up of spindle cells with hyperchromic large nuclei and pink cytoplasm intermingled with large cells with markedly pleomorphic nuclei and abundant cytoplasm along with prominent mitotic activity. Tumour cells revealed positive staining for Ki67 (25%), Oligo2 (focal), GFAP (focal), SMA (focal); negative immunoreactivity for EMA, CD34, Bcl-2, TTF1. Pathological diagnosis: Gliosarcoma, grade IV. Conclusions: Gliosarcoma is an extremely rare neoplasm with an aggressive biological behavior. In terms of histopathology, gliosarcomas are characterized by a biphasic tissue pattern with alternating areas displaying glial and mesenchymal differentiation.   Keywords Gliosarcoma, glioblastoma multiforme, brain neoplasm. References [1] World Healh Organization, WHO Classification of Tumors of the Central Nervous System, International Agency for Research on Cancer (IARC) 69372 Lyon Cedex 08, France, 2016. [2] F. A. Hashmi, A. Salim, M. Shamim, M. Bari, Biological Characteristics and Outcomes of Gliosarcoma, The Journal of the Pakistan Medical Association, Vol. 68, No. 8, 2018, pp. 1273-1275. [3] P. Giglio, M. R. Gilbert, Encyclopedia of the Neurological Sciences (Second Edition), MA: Academic Press/Elsevier, Waltham, 2014. [4] R. K. Kevin, M. Anand, S. M. John, Adult Gliosarcoma: Epidemiology, Natural History, and Factors Associated with Outcome, Neuro Oncol, Vol. 11, No. 2, 2009, pp. 183-191, https://doi.org/10.1215/15228517-2008-076. [5] L. Han, X. Zhang, S. Qiu et al., Magnetic Resonance Imaging of Primary Cerebral Gliosarcoma: A Report of 15 Cases, Acta Radiologica, Vol. 49, No.9, 2008, pp. 1058-1067, doi:10.1080/02841850802314796. [6] D. N. Louis, H. Ohgaki, O. D. Wiestler et al., The 2007 WHO Classification of Tumours of the Central Nervous System, Acta Neuropathologica, Vol. 114, No. 2, 2007, pp. 97-109, doi:10.1007/s00401-007-0278-6. [7] L. Seth, P. Arie, I. James et al., Greenfield’s Neuropathology (Ninth Edition), CRC Press, Boca Raton, Florida, 2015. [8] L. Cervoni, P. Celli, Cerebral Gliosarcoma: Prognostic Factors, Neurosurgical Review, Vol. 19, No. 2, 1996, pp. 93-96, https://doi.org/10.1007/bf00418077. [9] J. Pardo, M. Murcia, G. Felip et al., Gliosarcoma: A Rare Primary CNS Tumor. Presentation of Two Cases, Reports of Practical Oncology & Radiotherapy, Vol. 15, No. 4, 2010, pp. 98-102, https://doi.org/10.1016/j.rpor.2010.05.003. [10] J. Lutterbach, R. Guttenberger, A. Pagenstecher, Gliosarcoma: A Clinical Study, Radiotherapy and Oncology, Vol. 61, No. 1, 2001, pp. 57-64, https://doi.org/10.1016/S0167-8140(01)00415-7. [11] B. K. Kleinschmidt, T. Tihan, F. Rodriguez, Diagnostic Pathology: Neuropathology (Second Edition), Elsevier, Philadelphia, 2016. [12] H. F. Irwin, W. G. Sidney, Sarcoma Arising in Glioblastoma of the Brain, Am J Pathol, Vol. 31, No. 4, 1955, pp. 633-653. [13] A. S. Awadalla, A. M. A. Essa, H. H. A. Ahmadi et al., Gliosarcoma Case Report and Review of the Literature, The Pan African Medical Journal, Vol. 35, No. 26, 2020, https://doi.org/10.3109/02841869709001353.